Associations between ERAP1 polymorphisms and susceptibility to ankylosing spondylitis: a meta-analysis. Issue 8 (August 2016) - Lee, Young; Song, Gwan
Abstract The aim of this study was to determine whether 11 polymorphisms of endoplasmic reticulum aminopeptidase 1(ERAP1) confer susceptibility to ankylosing spondylitis (AS). The authors conducted meta-analyses on associations betweenERAP1 polymorphisms and AS susceptibility by using fixed and random effects models. A total of 19 articles were included in this meta-analysis, which comprised a total of 19, 902 AS patients and 39, 750 controls. The meta-analysis revealed a significant association between AS and the minor alleles of thers30187 polymorphism in all study subjects (OR = 1.255, 95 % CI = 1.147–1.373, P  = 8.0 × 10−8 ). Stratification by ethnicity led to the identification of a significant association between this polymorphism and AS in European patients (OR = 1.283, 95 % CI = 1.237–1.331, P  < 1.0 × 10−9 ). Meta-analyses of the results for thers27044, rs10050860, rs2287987, rs17482078, andrs26653 polymorphisms showed the same pattern that was found forrs30187 . Interestingly, thers27037 polymorphism was significantly associated with AS susceptibility in both European and Asian patients. Meta-analysis showed a significant association between AS and the minor alleles of thers27980 andrs27582 polymorphisms in the East Asian patients (OR = 0.904, 95 % CI = 0.818–0.999, P  = 0.047; OR = 0.871, 95 % CI = 0.772–0.982, P  = 0.024, respectively) (Table 2). However, these polymorphisms have not been studied in Europeans. This meta-analysis shows that theERAP1 polymorphisms are associated with the development of AS in Europeans and East Asians.